Personality Disorder in Pharaoh: An Analysis of the Story of the Pharaoh in the Quran - Linda Wahyuni Adam; Dhur Anni; Muhammad Yuchbibun Nury; Achmad Syariful Afif; Ifadah (al-Afkar, Journal For Islamic Studies, 2025)
Pharaoh is a title for the king of Egypt that is often coupled with the story of the Prophet Moses. With the strongest opinion stating that the Pharaoh at the time of the Prophet Moses was Ramesses II. He was the king of Egypt who held the longest power and was very obsessed with power. Various ways were done to realize his wishes, even though it harmed many people. The Quran recorded Pharaoh's actions that were beyond the limits of humanity, including; QS. an-Nazi'at: 24 (claiming to be God), QS. al-Baqarah: 49 (killing sons), QS. Taha: 71 (crucifying the hands of sorcerers), and QS. al-Qasas: 4 (dividing the people of Egypt). All of these atrocities were committed when Pharaoh held power. By using library research method and maudhu'i interpretation method, this article examines Pharaoh's cruel behavior from psychology, namely, personality disorder theory. It can be concluded that the mufasirs describe Pharaoh's personality as arrogant and dictatorial. Because of his personality, Pharaoh committed many cruel behaviors. Based on psychology, Pharaoh's behavior is included in abnormal behavior, he has a personality disorder based on characteristics including: acting violently (QS. al-Baqarah: 49), feeling fear (QS. al-Ghafir: 71), trying to influence individuals by controlling all subconscious desires and ideas (QS. al-Qasas: 4), never feeling guilty and sorry after hurting or harming others, having many requests (QS. al-A'raf: 106 and 134, QS. Taha: 58, QS. al-Qasas: 38), and selfishness.